Development of a microcontroller and resistive touchscreen-based speed monitoring and control system for DC motor - Adebisi, Oluwaseun Ibrahim; Ogundare, Ayoade Benson; Erinosho, Tolulope Christiana; Sonola, Moyosoluwalorun Odunayo; Adesanu, Adesewa Rofiat (Institute of Advanced Engineering and Science, 2023)
Speed control is a key requirement in direct current (DC) motor applications where accuracy, reliability, flexibility, and safety are of high importance. In this study, a microcontroller and resistive touchscreen-based DC motor speed monitoring and control system were developed. The core components employed in the development of the system include Arduino ATMega328P microcontroller, thin film technology (TFT) resistive touch screen, L293D motor driver, and infrared (IR) sensor module. ATMega328P microcontroller is the brain of the system around which the overall circuit design was modeled. TFT resistive touch screen displays the motor speed and also, enables the users to set a desired speed. L293D motor driver regulates the voltage and current supplied to the motor, and a feedback loop comprising an IR sensor module ensures the maintenance of the motor speed at the desired level. A performance test was conducted on the developed system to ascertain its correct functionality. The developed speed monitoring and control system operated satisfactorily during testing; achieving a speed control in the range of 800 to 3000 rpm. The developed device is useful and can be scaled up for various domestic and industrial applications.